Educational Gothic: Interrogating Violent Educations in Australian, Canadian and United States Fictions 1960-present - Jenkinson, Jade (2024)
My thesis examines depictions of education within bildungsroman-style Gothic novels and films produced in the United States, Australia, and Canada. I coin the label “Educational Gothic” to define these works. The shared context of settler colonialism is the critical foundation for my comparative analysis. If the bildungsroman has been central to burgeoning settler nations in solidifying a national character and establishing a sense of tradition, I examine its reverse in the Educational Gothic mode. I theorise that the Gothic institution reoccurs as a means of depicting and interrogating violent educational histories within these three nations, particularly when they are not present within official rhetoric. However, the relationship between history and representation is never clear-cut, and creates dynamic instabilities within creative productions. Thus, from 1960 to the present, this thesis charts the emergence and development of the Educational Gothic mode in film and literature, exploring how authors respond to the socio-political climate and examine identity, history and tradition through educational narratives. I delineate two strands of the Educational Gothic mode, Settler and Indigenous, and pay close attention to how these creatives respond to genocidal settler-colonial educational policies towards Indigenous peoples and women’s educational experiences in patriarchal institutions.